Optimization of air suspension coating for odour masking of fish bone powder: A nutritional formulation-based approach - Umesh Kumar Atneriya; Virendra Singh Yadav (Food and Humanity, 2026)

A systematic PCR-based framework for amplification of long and multi-exonic genes in non-model insects: : A case study of Bemisia tabaci Asia II 1 - C. N. Rajarushi; Amit Umesh Paschapur; Sai Manoj Marella; Muthuganeshan Annamalai; J. S. Pavan; Arunesh Kumar; Ramcharan Bhattacharya; Sabtharishi Subramanian (Molecular Biology Reports, 2026)

Tumor microenvironment in breast cancer: cellular crosstalk, pathways, and therapeutic insights - Manjari Sharma; Umesh Kumar; Shoorvir Singh (Molecular Biology Reports, 2026)

Chitosan and naringenin-coated silver nanoparticles as a nanoplatform against drug-resistant uropathogens - Ashu Devraj; Umesh Chand; Apurva Singh; Pramod Kumar Kushawaha (Brazilian Journal of Microbiology, 2026)

Sustainable valorization of pomegranate peel via ultrasound-assisted process optimization and its application in edible coatings for shelf-life extension of pomegranate arils - Reetika Joshi; Umesh C. Lohani; Anupama Singh; A.K. Verma; Saloni Joshi; Sanjay Kumar; Afzal Hussain; Bon Heun Koo; Anjuli Agarwal (Journal of Stored Products Research, 2026)

Next generation risk assessment and new approach methodologies for sustainable management of heavy metal contaminated environments: A critical review - Prince Kumar Singh; Indrajeet Kumar; Umesh Kumar; Rahul Prasad Singh; Ram Sharan Singh; Rajesh Kumar Sharma (Environmental Pollution, 2026)

Mapping of microplastic toxicity: Uptake, trophic transfer, and ecotoxicological risks in marine ecosystems - Prince Kumar Singh; Nisha Singh; Indrajeet Kumar; Umesh Kumar; Akanksha Dwivedi; Priyanka Singh; Saumya Mishra; Khushboo Pal; Avanish Prajapati; Rajesh Kumar Sharma (Aquatic Toxicology, 2026)

Ethnopharmacological exploration of Indian medicinal plants: from traditional knowledge to modern medicine - Indrajeet Kumar; Sachin Kumar Vishwakarma; Prince Kumar Singh; Umesh Kumar; Rahul Prasad Singh; Parvati Madheshiya; Akanksha Dwivedi; Priyanka Singh; Rajesh Kumar Sharma (Phytochemistry Reviews, 2026)

Adaptive responses of Gladiolus grandiflora L. to Soil and Hydroponic Systems: Morphological, Physiological, Anatomical and Molecular Perspectives - Piyush Verma; Mohit Yadav; Debashree Pattanaik; Umesh Chandra Sahoo; Sonik Anto; Soumit Kumar Behera; Jibankumar Singh Khuraijam; Chandra Sekhar Mohanty (Journal of Plant Growth Regulation, 2026)

Fourier transform infrared spectroscopy to evaluate the photo-stability and acid degradation behavior of indinavir sulphate: A sustainable approach in pharmaceutical analysis - Aparna Shekhar; Umesh Kumar; Meenu Sarbhai; Sobinder Singh; Parul Singh; Ranjana Mehrotra (Next Research, 2026)

Seasonal variation of microcystin-LR and associated health risks in and around Hirakud Reservoir, India - Ashish Kumar Sahu; Sawan Kumar Sahoo; Pralaya Biswas; Showkat Ahmad Mir; Binata Nayak; Pradeep Kumar Naik; Umesh Chandra Naik; Iswar Baitharu (Environmental Science and Pollution Research, 2026)

Evaluating Reference Evapotranspiration ( ETo ) Calculation Methods and Quantifying Climate‐Driven Change in Irrigation Demand Across Nepal's Terai - Umesh Kumar Sujakhu; Rajesh Khatakho; Naresh Suwal; Ayush Poudel (International Journal of Climatology, 2026)
Global food security faces growing pressure from population growth and climate change. Improving water productivity requires optimizing irrigation through accurate reference evapotranspiration (ETo) estimates, yet selecting reliable ETo methods remains difficult in data‐scarce Nepal. This study evaluates ETo in the Terai region of Nepal using data from 14 meteorological stations over a historical period (1989–2014) using nine empirical and physically based methods. Coupled Model Intercomparison Project Phase 6 (CMIP6) Global Climate Models (GCMs) data for temperature and precipitation under Shared Socioeconomic Pathways (SSP) SSP245 and SSP585 scenarios were used after downscaling and bias correction to develop a multi‐model ensemble for near (2027–2051), mid (2052–2076), and far‐future (2077–2100) periods. Using these projections, ETo, crop water requirement (CWR), and irrigation water requirements (IWR) were estimated and compared with historical conditions. Among the evaluated models, the Turc (TU) model consistently outperformed the other models, confirming its robustness for ETo estimation. Climate projections indicate increased winter precipitation, particularly under the SSP585 far‐future scenario, alongside rising maximum and minimum temperatures across all scenarios, with stronger warming during winter than the monsoon season. The highest ETo occurred from April to June, and overall ETo is projected to increase under both scenarios, with a pronounced rise (40.7%) in January under SSP585, while slight monsoon‐season declines (0.2%–2.3%) are projected under SSP245. CWR peaks during July–September, with the highest values observed in July. Notable increases in CWR are projected in July under SSP585 mid‐ and far‐future scenarios and during winter across all scenarios. IWR exhibits strong seasonality, peaking in the monsoon months, with most stations showing moderate annual increases (5%–14%), although some stations experience substantial declines (13%–36%). Overall, the results highlight strong spatial heterogeneity in future irrigation demand, emphasizing the need for region‐specific, climate‐resilient water management strategies across the Terai.

Cellular redox disruption and apoptosis: Differential effects of RFR frequencies on Leydig cells - Pooja Jangid; Umesh Rai; Jayesh Kumar Sevak; Sanjay Singh; Rajeev Singh (Toxicology and Applied Pharmacology, 2026)

Agro-waste amendments alleviate nickel stress: insights into growth, physiology, metabolites, bioaccumulation and health risk assessment in wheat under tropical ecosystems - Umesh Kumar; Prince Kumar Singh; Indrajeet Kumar; Rajesh Kumar Sharma (Physiology and Molecular Biology of Plants, 2026)

Benthic meiofaunal community structure from a recently discovered hydrothermal field on a seamount, Andaman Sea, Indian Ocean - Gourav Kumar Mishra; Sabyasachi Sautya; Sriram Gullapalli; Pawan Dewangan; Umesh Pradhan; Gunjan Sarkar; Sanofar Khokar; Amita Choudhury (Marine Biology, 2026)

Genome-Wide SNP and Selective Sweep Analyses Identify Key Genes Associated with Adaptation and Economic Traits in Indian Gir Cattle - Raja Thiruvothur Venkatesan; Singh Umesh; Kumar Sushil; Singh Amit Kumar; Alex Rani (Agricultural Research, 2026)

Decadal analyses of macrobenthos of a tropical estuary: spatio-temporal shifts, trends and ecological assessment - Maaz Shaikh; Soniya Sukumaran; J Mariyam Johna; Umesh Kumar Pradhan (Environmental Monitoring and Assessment, 2026)

Cyclodextrins: Synthesis, Pharmaceutical Applications, Drug Delivery Systems and Safety Perspectives - Aman Kumar; Ravi Raj Pal; Preeti Patel; Atul Jain; Nitin Sharma; Umesh Kumar Patil; Balak Das Kurmi (AAPS PharmSciTech, 2026)

Transglutaminase-assisted development of millet-legume-based mock meat - Riya Joshi; Umesh C. Lohani; Navin Chandra Shahi; Ashok K. Verma; Atul Singh; Iqbal Hussain; Sanjay Kumar (Food and Humanity, 2026)

Assessing Soil Fertility Mapping Using Geospatial Techniques and Artificial Intelligence - Umesh Chandra; Gaurav Shukla; Himani Maheshwari; Sachin Kumar; Rajesh Singh; Anita Gehlot; Amit Kumar Thakur (Journal of the Indian Society of Remote Sensing, 2026)

Mycoremediation: a sustainable approach for environmental cleanup — a review - Ayush Gaur; Priyanka Yadav; Ravi Shanker; Umesh Kumar Singh; Anupriya Chaudhary; Saba Ehsan; Mohan P. Singh (Environmental Science and Pollution Research, 2026)

Craniometaphyseal dysplasia with severe maxillary hypoplasia due to ANKH gene mutation: A case report - Umesh Kumar; Saugat Ray; Amrit Thapa; Baljinder Singh Walia; Barun Kumar Chakrabarty (Journal of Genetics, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Early Detection of Potato Leaf Diseases with PotatoNet-X: A Deep Learning Model Combining ResNet, DenseNet, and Attention Mechanisms - Umesh Kumar Lilhore; P. Kavitha; Swetha G.; Sunder R.; Sarita Simaiya; Ehab Seif Ghith; Shimaa A. Hussien (Potato Research, 2026)

Multiplex Real Time PCR Assay Targeting the eqbE for Rapid Detection and Differentiation of Streptococcus equi from Other Streptococcus Species in Indian Equines - Dharvi Chhabra; Juhi Nagra; Anju Manuja; Rajesh Dahiya; Minakshi Prasad; Umesh Goutam; Balvinder Kumar (Indian Journal of Microbiology, 2026)

Polyherbal Formulation Attenuates Isoproterenol-Induced Cardiac Toxicity Through Regulation of Mitochondrial Bioenergetics, Lipid Toxicity, and Intrinsic Apoptotic Pathways in Rats - V V Sathibabu Uddandrao; S. Nivetha; P. Chandrasekaran; S. Sengottuvelu; Brahma Naidu Parim; Umesh Kumar; Andamuthu Yamunadevi; Kaushik Das (Cell Biochemistry and Biophysics, 2026)

Phosphorus speciation and bioavailability in the hyperdynamic gulf of Khambhat: Impacts of terrestrial inputs and hydrodynamics - T K Vyshnavi; Umesh Kumar Pradhan; Balaram Sahu (Marine Pollution Bulletin, 2026)

Elemental and isotopic constraints on organic matter source shifts in a tropical urbanized estuary–creek system - Balaram Sahu; Umesh Kumar Pradhan (Marine Pollution Bulletin, 2026)

Climate-resilient agri-food systems: analyzing yield trends and overcoming adoption barriers - Shubham Durgude; Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Dinesh Chand Meena; Suneel Kumar; Illathur R. Reddy; et al. (Environment, Development and Sustainability, 2026)

Microbial and pathogenic indicators for pollution risk assessment in an urban estuary under dry and wet conditions - Lawrance Irudayarajan; Chinnarajan Ravindran; Umesh Kumar Pradhan; Seyieleno C. Seleyi; Balaram Sahu; Soniya Sukumaran; Chellandi Mohandass (Regional Studies in Marine Science, 2026)

Valorization of lignin to produce nanofibers of industrial importance - Deepak Sharma; Neha Sharma; Lohith Kumar Dasarahally Huligowda; Mridul Umesh; Preeti Sharma; Pritha Chakraborty; Suma Sarojini; Charumathi Jayachandran; Ritu Pasrija; Vinay Kumar (Bioresource Technology, 2026)

Unfolding pesticide toxicity: food safety, health risk, and sustainable agriculture - Umesh Kumar; Om Sajeevan Patel; Shahil Siddiqui; Kewat Sanjay Kumar; Sheo Mohan Prasad (Vegetos, 2025)

Effect of storage conditions on the proximate composition, mineral retention, and phenolic contents of millet and chicken-based nutri-cereal mix - Samiksha Sharma; Pankaj Gautam; Arun Kumar; Harish Chandra Joshi; Ankita Dobhal; Umesh Chandra Lohani; Waseem Ahmad; Sanjay Kumar (Food and Humanity, 2025)

Real-time non-destructive monitoring of concrete curing and strength development using hyperspectral remote sensing - Ishtiaq Ahmed; Umesh Kumar Sharma; Pradeep Kumar Garg (Innovative Infrastructure Solutions, 2025)

Regulatory dynamics of Th17 lymphocytes in oral squamous cell carcinoma: immune modulation and emerging immunotherapies - Umesh Kumar; Mansi Kumari; Gagandeep Singh; Neelam Thakur (Immunologic Research, 2025)

Nickel Contamination in Terrestrial Ecosystems: Insights into Impacts, Phytotoxicity Mechanisms, and Remediation Technologies - Umesh Kumar; Indrajeet Kumar; Prince Kumar Singh; Akanksha Dwivedi; Priyanka Singh; Saumya Mishra; Chandra Shekhar Seth; Rajesh Kumar Sharma (Reviews of Environmental Contamination and Toxicology, 2025)

Assessing long-term vegetation changes, pollution and climate response in the Uttarakhand Region, North India: implications of Google Earth Engine - Umesh Chandra Dumka; Kiran Rawat; Dimitris G. Kaskaoutis; Ankur Srivastava; Muhammad Bilal; Sanjeev Kimothi; Prasun Kumar Gupta; Nikul Kumari (Environmental Monitoring and Assessment, 2025)

Pathways of heavy metal(loid) pollution and health risk assessment of a transboundary river basin system - Rachna; Umesh Kumar Singh; Prashant; Shreerup Goswami (Environmental Monitoring and Assessment, 2025)

Assessment of Factors Influencing Farmers’ Choices of Marketing Channels for Kiwifruit (Actinidia deliciosa A. Chev.): Insights from the Indian Himalayan Region - Shilpa Sharma; Rakesh Kumar Gupta; Ashu Chandel; Vishal Singh Rana; Subhash Sharma; Neeraj Sankhyan; Umesh Sharma (Environment, Development and Sustainability, 2025)

Origin and evolution of synchronous Miocene leucogranite dykes and porphyritic granitoid pluton in the Tangste region of Pangong metamorphic complex, Ladakh Trans-Himalaya, India: Constraints from geochemistry and zircon U-Pb-Hf isotopes - Sita Bora; Santosh Kumar; Kapil S. Panwar; Keewook Yi; Youn-Joong Jeong; Umesh K. Sharma (Lithos, 2025)

Biochemical profiling, anti-biofilm, and anti-quorum sensing activities of Psophocarpus tetragonolobus (L.) DC. root-tuber - Rayees Ahmad Lone; Umesh Chandra Sahoo; Anoop Shakya; Nem Kumar Ngpoore; Nasreen Bano; Rojalin Pattanayak; Brahma N. Singh; Chandra Sekhar Mohanty (Natural Product Research, 2025)

Intelligent waste sorting for sustainable environment: A hybrid deep learning and transfer learning model - Umesh Kumar Lilhore; Sarita Simaiya; Surjeet Dalal; Magdalena Radulescu; Daniel Balsalobre-Lorente (Gondwana Research, 2025)

Mitigating fire resistance losses in corroded reinforced concrete columns using a hybrid fibers approach - Shashank Chandra; Umesh Kumar Sharma (Engineering Structures, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Geospatial monitoring of peri-urban zones in Chandigarh through multi-year landsat imagery - Jyoti Saini; Umesh Kumar; Anil Kumar Gupta; Parul Mishra; Ratchagaraja Dhairiyasamy; Deekshant Varshney; Subhav Singh (Urban Ecosystems, 2025)

A comprehensive insight into the ethnopharmacology, phytochemistry and therapeutic profile of Moringa oleifera Lam. - Khushi Gupta; Avadh Biharee; Neha Bhatia; Umesh Kumar Patil; Suresh Thareja (Phytochemistry Reviews, 2025)

Unlocking the Impending Role of Automation in Fruit Production: An Overview - Arun Kumar; Sunny Sharma; Umesh Sharma; Vishal S. Rana; Vikanksha Thakur; Neha Sharma; Ankit; Prachi; Himanshu; Shivender Thakur (Applied Fruit Science, 2025)

Stimulatory effects of Ultraviolet-B irradiation on bioactives, phenolics, beta-glucans, vitamin D2 and antioxidant activities in submerged fermented Pleurotus eryngii mycelia - Umesh Singh; Ravi Kant; Arinjay Kumar Jain; Satyawati Sharma (Food Bioscience, 2025)

Investigating Root-Tuberization in Underutilized Legume Psophocarpus tetragonolobus (L.) DC. and Revealing the Role of Calcium-Dependent Protein Kinase in this Process - Rayees Ahmad Lone; Nasreen Bano; Shafquat Fakhrah; Umesh Chandra Sahoo; Shahre Aalam; Sumit Kumar Bag; Rojalin Pattanayak; Chandra Sekhar Mohanty (Journal of Plant Growth Regulation, 2025)

HPTLC and LCMS based investigation of ethanolic leaf extracts of Nerium oleander and identification of quercetin as potent compound targeting plasmodium proteases: An analytical and in silico approach - Rajesh Tiwari; Mohammad Khalid Parvez; M.Arockia Babu; Mohammed S. Al-Dosari; Thakur Gurjeet Singh; Kapil Kumar Goel; Nemat Ali; Yogita Tyagi; Umesh Yadav; Bhupinder Kumar; Nisha Bansal (South African Journal of Botany, 2025)

Development and characterization of carrageenan-based antibacterial films incorporated with natural melanin pigment from niger seed hulls (Guizotia abyssinica) and their efficacy to enhance the shelf-life of strawberries - B.T. Sunil Kumar; Jeevan Prasad Reddy; V. Vanajakshi; Akshay H. Dasalkar; Sudheer Kumar Yannam; Umesh H. Hebbar; Sridevi Annapurna Singh (Food Control, 2025)

Spatio-temporal analysis of air pollution and meteorological influences in western Uttar Pradesh using Geospatial techniques: insights for policy and management - Ram Pravesh Kumar; Aafreen Jahan; Ranjit Singh; Pradeep Kumar; Rajesh Bag; Rajeev Bhatla; Balram Ambade; Umesh Chandra Dumka (International Journal of Remote Sensing, 2025)

Enhanced hydrogen evolution performance of magnesium-doped molybdenum disulfide nanosheets under acidic conditions - K. Harikrishnan; Ariful Hoque; Rajendra Patel; Umesh Kumar Gaur; Manu Sharma (Journal of Environmental Chemical Engineering, 2025)

Phenotypic, Biochemical and Molecular Characterization of Streptococcus equi Isolates in Northern India - Dharvi Chhabra; Juhi Nagra; Anju Manuja; H. S. Singha; R. K. Vaid; Umesh Goutam; Balvinder Kumar (Indian Journal of Microbiology, 2025)

Buzzing for Broccoli (Brassica oleracea var. italica): Exploring Insect Pollinators, Their Behaviour, Single-Visit Efficiency and the Significance of Honey Bees in Yield Enhancement - Sunaullah Bhat; Johnson Stanley; A. R. N. S. Subbanna; Amit Umesh Paschapur; Jaiprakash Gupta; Sandeep Kumar (Agricultural Research, 2025)

Characterization of metabolite profiles in milk derived exosomes from indicus, crossbred and taurine cows by proton nuclear magnetic resonance analysis - Vidhi Garg; Manishi Mukesh; Umesh Kumar; Dinesh Kumar; Amarjeet; Ritu Mahajan; Ranjit S. Kataria; Parvesh Kumari; Monika Sodhi (Food Chemistry, 2025)

Retraction notice to “Emerging challenges for the agro-industrial food waste utilization: A review on food waste biorefinery” [Bioresour. Technol. 362 (2022) 127790] - Vinay Kumar; Neha Sharma; Mridul Umesh; Manickam Selvaraj; Badria M. Al-Shehri; Pritha Chakraborty; Lucky Duhan; Shivali Sharma; Ritu Pasrija; Mukesh Kumar Awasthi; Siva Ramakrishna Lakkaboyana; Rodrigo Andler; et al. (Bioresource Technology, 2025)

Insights into Cadmium Uptake and Changes in Morphophysiological and Biochemical Characteristics of Eclipta alba L., Plants Exposed to Elevated Cadmium in Soil - Akanksha Dwivedi; Prince Kumar Singh; Umesh Kumar; Indrajeet Kumar; Priyanka Singh; Rajesh Kumar Sharma (Journal of Soil Science and Plant Nutrition, 2025)

Impact of EEG Reference Schemes on Event-Related Potential Outcomes: A Corollary Discharge Study Using a Talk/Listen Paradigm - Subham Samantaray; Nishant Goyal; Muralidharan Kesavan; Ganesan Venkatasubramanian; Anushree Bose; Umesh Shreekantiah; Vanteemar S. Sreeraj; Manul Das; Justin Raj; Sujeet Kumar (Brain Topography, 2025)

Frontiers in superbug management: innovating approaches to combat antimicrobial resistance - Priyanka Chambial; Neelam Thakur; Prudhvi Lal Bhukya; Anbazhagan Subbaiyan; Umesh Kumar (Archives of Microbiology, 2025)

Revolutionizing air quality forecasting: Fusion of state-of-the-art deep learning models for precise classification - Umesh Kumar Lilhore; Sarita Simaiya; Surjeet Dalal; Neetu Faujdar (Urban Climate, 2025)

In-silico evaluation of Cassia occidentalis phytochemicals for Plasmodium falciparum plasmepsin V inhibition: Revealing antimalarial potential - Aliyu Usman Maaji; Ramgopal Dhakar; Pankaj Kumar Teli; Umesh Garu; Umar Aliyu Adamu; Saminu Saminu Muhammad; Khalipha Ali Jubril; Fatima Idris Sambo (South African Journal of Botany, 2025)

Effect of dwarfism and endogenous gibberellin modulation via growth regulators on heat stress tolerance in wheat - Shivani Nagar; V.P. Singh; Rajkumar Dhakar; Ajay Arora; Deepika Kumar Umesh; Ekta Joshi; Chandana Behera; Ravi Prakash Saini (South African Journal of Botany, 2025)

Exploration of morphological diversity to select naturally occurring promising walnut (Juglans regia L.) genotypes from the North-Western Himalayan region - Umesh Sharma; Hari Paul Sankhyan; Vishal Singh Rana; Rajesh Sharma; Anita Kumari; Rajneesh Kumar; Parul Sharma; Balkrishna Tiwari; Shikha Thakur; Neeraj Sankhyan; Sunny Sharma; Shilpa Sharma (South African Journal of Botany, 2025)

Mechanical performance of cement concrete with use of combined fibers of basalt and bamboo - Sachin Kumar; Umesh Sharma (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Characterizing metabolome signature of colostrum, transition and mature milk of indigenous cows (Bos indicus) adapted to high altitude environment of Leh-Ladakh - Amarjeet; Umesh Kumar; Monika Sodhi; Dinesh Kumar; Prince Vivek; Saket K. Niranjan; Ranjit Singh Kataria; Sudarshan Kumar; Manish Sharma; Manish Tiwari; Rajeev A.K. Aggarwal; Vijay K. Bharti; et al. (Food Chemistry, 2025)

Synergistic effects of partially purified transglutaminase from Asian seabass liver and plant protein isolates on gelation, cross-linking, molecular interactions and rheological properties of sardine surimi proteins - Akanksha R Gautam; Soottawat Benjakul; Umesh Patil; Vijay Kumar Reddy Surasani; Pornpot Nuthong; Avtar Singh (Food Bioscience, 2025)

Fish waste valorisation through production of biodiesel and biopolymers for sustainable development: A mini review - Mridul Umesh; Vinay Kumar; Kumaresan Priyanka; Preethi Kathirvel; Sreehari Suresh; Adhithya Sankar Santhosh (Bioresource Technology Reports, 2025)

Factors affecting smallholder farmers’ adaptive capacity to climate change: A comparative study of Nepal, India, and Bangladesh - Prem Sagar Chapagain; Tibendra Raj Banskota; Shobha Shrestha; Yili Zhang; Jianzhong Yan; Suresh Chand Rai; Md Nurul Islam; Linshan Liu; Umesh Kumar Mandal; Basanta Paudel; Narendra Raj Khanal; Om Chandra Thasineku (Journal of Geographical Sciences, 2025)

A framework for implementation of environmental flow requirements through community perceptions – the case of Bargi Dam, Jabalpur District, Madhya Pradesh - Govind M. P.; Rama Umesh Pandey; Pradeep Kumar (Hydrological Sciences Journal, 2025)

Potential health, environmental implication of microplastics: A review on its detection - Bhawana Yadav; Payal Gupta; Vinay Kumar; Mridul Umesh; Deepak Sharma; Jithin Thomas; Suraj Kumar Bhagat (Journal of Contaminant Hydrology, 2025)

Exploring the valorization of fruit bio-waste for sustainable utilization in agro-food industries: A Comprehensive Review - Sunny Sharma; Umesh Sharma; Neha Sharma; Vishal Singh Rana; Shivender Thakur; Amit Kumar; Rupesh Kumar (Food Bioscience, 2025)

Macrobenthic assemblages of anthropogenically active subtidal zones contiguous to a marine protected area: a 9-year revisit - Soniya Sukumaran; Jisna Joy; Hurmine Ridha; Umesh Kumar Pradhan; Satej Pawar (Environmental Science and Pollution Research, 2024)

Dissolved and suspended nutrient complexity in an urbanized creek-estuary confluence: Implication on water quality alteration - Balaram Sahu; Umesh Kumar Pradhan; Udayakrishnan P.B.; Priyanka Bambaras (Marine Pollution Bulletin, 2024)

Metagenomic analysis of soil from landfill site reveals a diverse microbial community involved in plastic degradation - Akhilesh Kumar; Sudarshan Singh Lakhawat; Kashmir Singh; Vikram Kumar; Kumar Sambhav Verma; Umesh Kumar Dwivedi; S.L. Kothari; Naveen Malik; Pushpender Kumar Sharma (Journal of Hazardous Materials, 2024)

Phenotypic characterization of core accessions of grain amaranth (Amaranthus hypochondriacus L.) - Jutika Boro; Umesh Kumar; Hemant Kumar Yadav (Genetic Resources and Crop Evolution, 2024)

Pesticide pollution: toxicity, sources and advanced remediation approaches - Rachna; Mohan Prasad Singh; Shreerup Goswami; Umesh Kumar Singh (Environmental Science and Pollution Research, 2024)

Phytochemical composition, antioxidant and antibacterial properties of methanol stem and leaf extracts of Croton bonplandianus Baill - Indrajeet Kumar; Umesh Kumar; Prince Kumar Singh; Jay Shankar Yadav; Akanksha Dwivedi; Priyanka Singh; Ashutosh Tripathi; Rajesh Kumar Sharma (Vegetos, 2024)

Characterization, antioxidant, and antimicrobial activity of melanin extracted from nigerseed hulls - B.T. Sunil Kumar; B.V. Sathyendra Rao; S. Swathi; V. Vanajakshi; H. Umesh Hebbar; Sridevi Annapurna Singh (Food Bioscience, 2024)

Development of sustainable slag-based alkali-activated concrete incorporating fly ash at ambient curing conditions - Shashwati Soumya Pradhan; Umesh Mishra; Sushant Kumar Biswal; Parveen Jangra (Energy, Ecology and Environment, 2024)

Critical review on toxic contaminants in surface water ecosystem: sources, monitoring, and its impact on human health - Prince Kumar Singh; Umesh Kumar; Indrajeet Kumar; Akanksha Dwivedi; Priyanka Singh; Saumya Mishra; Chandra Shekhar Seth; Rajesh Kumar Sharma (Environmental Science and Pollution Research, 2024)

Phenotypic and transcriptomics characterization uncovers genes underlying tuber yield traits and gene expression marker development in potato under aeroponics - Rasna Zinta; Jagesh Kumar Tiwari; Tanuja Buckseth; Umesh Goutam; Rajesh Kumar Singh; Ajay Kumar Thakur; Shwetank Singh; Vinod Kumar; Manoj Kumar (Planta, 2024)

Hazard identification of endocrine-disrupting carcinogens (EDCs) in relation to cancers in humans - Neha Sharma; Vinay Kumar; Vimal S.; Mridul Umesh; Preeti Sharma; Basheer Thazeem; Komalpreet Kaur; Jithin Thomas; Ritu Pasrija; Divya Utreja (Environmental Toxicology and Pharmacology, 2024)

Defining genomic landscape for identification of potential candidate resistance genes associated with major rice diseases through MetaQTL analysis - Simran Goyal; Dinesh Kumar Saini; Pankaj Kumar; Gurwinder Kaur; Umesh Preethi Praba; Krishna Sai Karnatam; Gautam Chhabra; Rajveer Singh; Yogesh Vikal (Journal of Biosciences, 2024)

Lignocellulosic biomass for biochar production: A green initiative on biowaste conversion for pharmaceutical and other emerging pollutant removal - Vinay Kumar; Neha Sharma; Balamurugan Panneerselvam; Lohith Kumar Dasarahally Huligowda; Mridul Umesh; Manish Gupta; Khursheed Muzammil; Yousef Zahrani; Musa Malmutheibi (Chemosphere, 2024)

Examining the effects of nano iron oxide on physical and mechanical characteristics of rubberized concrete - Raman Saini; Gyanendra Kumar Chaturvedy; Umesh Kumar Pandey (Innovative Infrastructure Solutions, 2024)

An adaptive mobility-aware secure handover and scheduling protocol for Earth Observation (EO) communication using fog computing - Navjeet Kaur; Ayush Mittal; Umesh Kumar Lilhore; Sarita Simaiya; Surjeet Dalal; Yogesh Kumar Sharma (Earth Science Informatics, 2024)

Melatonin Inhibits AGS Cell Proliferation by Binding to the ATP Binding Site of CDK2 Under Hyperglycemic Conditions - Abhishek Chatterjee; Tapasi Roy; Deeti Jyothi; Vineet Kumar Mishra; Umesh Prasad Singh; Snehasikta Swarnakar (Cell Biochemistry and Biophysics, 2024)

Diversity of haemoparasites in migratory small ruminants of Himalayas, India - Gopinath Devi; Putan Singh; Umesh Dimri; Siju Susan Jacob; Gauri Jairath; Jobin Jose Kattoor; P. Preena; Y. Ajith; Gorakh Mal; Rinku Sharma; Surender Kumar; Rajni Chaudhary; et al. (Small Ruminant Research, 2024)

Mulberry: From nutraceuticals to bioactive phytochemicals - Venkatesh Kumar R.; Wouatsa Nangue Arlette Vyry; Seema Chauhan; Vandana Singh; Devika Srivastava; Umesh Kumar; Ritu Raj; Abhishek Verma (Food and Humanity, 2024)

Investigating the wave attenuation capabilities of rectangular pile head breakwater: A physical modelling approach - Arunakumar Hunasanahally Sathyanarayana; Praveen S. Suvarna; Vinay Kumar Yadav Banagani; Pruthviraj Umesh; Kiran G. Shirlal (Ocean Engineering, 2024)

Transcriptome profiling and characterization of genes associated with tuberization under high temperature in aeroponics in potato cv. Kufri Anand - Rasna Zinta; Jagesh Kumar Tiwari; Tanuja Buckseth; Umesh Goutam; Rajesh Kumar Singh; Vinod Kumar; Ajay Kumar Thakur (Genes & Genomics, 2024)

Commercialization potential of PET (polyethylene terephthalate) recycled nanomaterials: A review on validation parameters - Vinay Kumar; Neha Sharma; Mridul Umesh; Roopali Sharma; Munish Sharma; Deepak Sharma; Munish Sharma; Sonica Sondhi; Jithin Thomas; Deepak Kumar; Lavish Kansal; Niraj Kumar Jha (Chemosphere, 2024)

Transboundary hazard and downstream impact of glacial lakes in Hindu-Kush Karakoram Himalayas - Saket Dubey; Ashim Sattar; Vivek Gupta; Manish Kumar Goyal; Umesh K. Haritashya; Jeffrey S. Kargel (Science of The Total Environment, 2024)

Soil-mustard revitalization via rice husk ash, a promising soil amendment material for sustainable management of heavy metal contamination in tropical ecosystem - Prince Kumar Singh; Indrajeet Kumar; Umesh Kumar; Rajesh Kumar Sharma (Journal of Environmental Management, 2024)

Screening of mustard cultivars for phytoremediation of heavy metals contamination in wastewater irrigated soil systems - Prince Kumar Singh; Jay Shankar Yadav; Indrajeet Kumar; Umesh Kumar; Rajesh Kumar Sharma (Environmental Monitoring and Assessment, 2024)

Captivating actions of pomological crops waste as biosorbents for environmental remediation: a comprehensive review - Sunny Sharma; Vandana Thakur; Vishal Singh Rana; Umesh Sharma; Shivender Thakur; Shivali Sharma; Sartaj Ahmed Bhat; Rupesh Kumar; Amit Kumar (Environmental Science and Pollution Research, 2024)

Optimizing mineral identification for sustainable resource extraction through hybrid deep learning enabled FinTech model - Magdalena Radulescu; Surjeet Dalal; Umesh Kumar Lilhore; Sarita Saimiya (Resources Policy, 2024)

Forecasting the Future of Papaya in India: Predicting Area and Production Through Autoregressive Integrated Moving Average - Shilpa Sharma; Rakesh Kumar Gupta; Vishal S. Rana; Neeraj Sankhyan; Umesh Sharma; Sunny Sharma (Applied Fruit Science, 2024)

A hybrid LBP-CNN with YOLO-v5-based fire and smoke detection model in various environmental conditions for environmental sustainability in smart city - Surjeet Dalal; Umesh Kumar Lilhore; Magdalena Radulescu; Sarita Simaiya; Vivek Jaglan; Ashish Sharma (Environmental Science and Pollution Research, 2024)

Bibliometric analysis, physical properties, and experimental evaluation of additives-diesel ternary blends - Chandan Kumar; Mukesh Kumar; Umesh Kumar Das; Sumit Sharma (Environmental Science and Pollution Research, 2023)

Synergistic interaction between hydrocolloids and kinnow peel biowaste for the development of edible fillers using response surface methodology - Bhawna Bisht; Umesh Chandra Lohani; Manisha Nanda; Sanjay Kumar; Mikhail Vlaskin; Anna Dsouza; Saloni Joshi; Vinod Kumar (Environmental Science and Pollution Research, 2023)

Highly sensitive detection of hazardous hydroquinone and chloramphenicol in the presence of paracetamol using cobalt tungstate (CoWO4) nanoplates modified electrode - Varun Pratap Singh; Gajendar Singh; Rajendra Patel; Umesh Kumar Gaur; Manu Sharma (Journal of Environmental Chemical Engineering, 2023)

Genetic analysis of early seedling vigour in Oryza glaberrima accessions under laboratory and direct-seeded rice conditions - Muralidhara Bharamappanavara; Anantha Siddaiah Madhyavenkatapura; Manoj Chikkahosahalli Appaiah; Basavaraj Siddanagouda Patil; Ajitha Vijjeswarapu; Ponnuvel Senguttuvel; Maganti Sheshu Madhav; Santosha Rathod; Tapan Kumar Mondal; Lokesha Ramappa; Umesh Rangappa Mathada; Raman Meenakshi Sundaram; et al. (Cereal Research Communications, 2023)

Understanding carbon sequestration trends using model and satellite data under different ecosystems in India - Smrati Gupta; Pramit Kumar Deb Burman; Yogesh K. Tiwari; Umesh Chandra Dumka; Nikul Kumari; Ankur Srivastava; Akhilesh S. Raghubanshi (Science of The Total Environment, 2023)

Black Carbon vs Carbon Monoxide: Assessing the Impact on Indian Urban Cities - Balram Ambade; Tapan Kumar Sankar; Sneha Gautam; Dilip Kumar Mahato; Umesh Chandra Dumka; Faruq Mohammad; Hamad A. Al-Lohedan; Ahmed A. Soleiman; Alok Sagar Gautam (Water, Air, & Soil Pollution, 2023)

Biomarker responses in the Coilia dussumieri exposed to petroleum hydrocarbons contamination in urbanized estuaries along the west coast of India - Molla Nageswar Rao; Adluri Anjaneyulu; Vaishnu Durga Parthipan; Anirudh Ram; Umesh Kumar Pradhan; Udaya Krishnan; Vidavalur Siddaiha (Environmental Geochemistry and Health, 2023)

A sustainable approach for the removal of pharmaceutical contaminants from effluent using polyamide thin-film composite membranes integrated with Zn-based metal organic frameworks - Arun Kumar Shukla; Javed Alam; Umesh Mishra; Mansour Alhoshan (Environmental Science and Pollution Research, 2023)

Enhancement in growth, yield and nutritive characteristics of strawberry (Fragaria × ananassa Duch.) by the application of biostimulant: seaweed extract - Vishal Singh Rana; Kusum Lingwal; Sunny Sharma; Neerja Rana; Ravina Pawar; Vijay Kumar; Umesh Sharma (Acta Physiologiae Plantarum, 2023)

Toxicity analysis of endocrine disrupting pesticides on non-target organisms: A critical analysis on toxicity mechanisms - Vinay Kumar; Neha Sharma; Preeti Sharma; Ritu Pasrija; Komalpreet Kaur; Mridul Umesh; Basheer Thazeem (Toxicology and Applied Pharmacology, 2023)

Identification and characterization of chitinase-producing bacteria from gut of pleurostict scarab beetle grubs (Coleoptera: Scarabaeidae) - Nutan Karki; Amit Umesh Paschapur; Avupati RNS Subbanna; Johnson Stanley; Ashish Kumar Singh; Ila Bisht; Jai Prakash Gupta (International Journal of Tropical Insect Science, 2023)

ABTCN: an efficient hybrid deep learning approach for atmospheric temperature prediction - Naba Krushna Sabat; Umesh Chandra Pati; Santos Kumar Das (Environmental Science and Pollution Research, 2023)

Micropollutants characteristics, fate, and sustainable removal technologies for landfill leachate: A technical perspective - Vinay Kumar; Neha Sharma; Mridul Umesh; Pritha Chakraborty; Komalpreet Kaur; Lucky Duhan; Suma Sarojini; B. Thazeem; Ritu Pasrija; Alisa S. Vangnai; Subhrangsu Sundar Maitra (Journal of Water Process Engineering, 2023)

Insights into the management of food waste in developing countries: with special reference to India - Ansuman Sahoo; Akanksha Dwivedi; Parvati Madheshiya; Umesh Kumar; Rajesh Kumar Sharma; Supriya Tiwari (Environmental Science and Pollution Research, 2023)

Correction to: Identification and validation of reference genes in vetiver (Chrysopogon zizanioides) root transcriptome - Abhishek Singh Chauhan; Madhu Tiwari; Yuvraj Indoliya; Shashank Kumar Mishra; Umesh Chandra Lavania; Puneet Singh Chauhan; Debasis Chakrabarty; Rudra Deo Tripathi (Physiology and Molecular Biology of Plants, 2023)

Role of Beneficial Elements in Developing Resilience to Abiotic and Biotic Stresses in Plants: Present Status and Future Prospects - Urvashi Mittal; Vijay Kumar; Sarvjeet Kukreja; Baljeet Singh; Narendra Kumar Pandey; Umesh Goutam (Journal of Plant Growth Regulation, 2023)

Effect of graphene oxide on the microscopic, physical and mechanical characteristics of rubberized concrete - Gyanendra Kumar Chaturvedy; Umesh Kumar Pandey; Harit Kumar (Innovative Infrastructure Solutions, 2023)

Potential arsenic–chromium–lead Co-contamination in the hilly terrain of Arunachal Pradesh, north-eastern India: Genesis and health perspective - Ritusmita Goswami; Chandrashekhar Bhagat; Igo Lollen; Nikita Neog; Umesh B. Barache; Ritu Thakur; Jurgen Mahlknecht; Manish Kumar (Chemosphere, 2023)

Identification and validation of reference genes in vetiver (Chrysopogon zizanioides) root transcriptome - Abhishek Singh Chauhan; Madhu Tiwari; Yuvraj Indoliya; Shashank Kumar Mishra; Umesh Chandra Lavania; Puneet Singh Chauhan; Debasis Chakrabarty; Rudra Deo Tripathi (Physiology and Molecular Biology of Plants, 2023)

Metal tolerance gene family in barley: an in silico comprehensive analysis - Umesh Kumar Tanwar; Ewelina Stolarska; Elżbieta Rudy; Ewelina Paluch-Lubawa; Magda Grabsztunowicz; Magdalena Arasimowicz-Jelonek; Ewa Sobieszczuk-Nowicka (Journal of Applied Genetics, 2023)
Metal-tolerance proteins (MTPs) are divalent cation transporters that play critical roles in metal tolerance and ion homeostasis in plants. However, a comprehensive study of MTPs is still lacking in crop plants. The current study aimed to comprehensively identify and characterize the MTP gene family in barley ( Hordeum vulgare , Hv ), an important crop. In total, 12 HvMTPs were identified in the barley genome in this study. They were divided into three phylogenetic groups (Zn-cation diffusion facilitator proteins [CDFs], Fe/Zn-CDFs, and Mn-CDFs) and further subdivided into seven groups (G1, G5, G6, G7, G8, G9, and G12). The majority of MTPs were hydrophobic proteins found in the vacuolar membrane. Gene duplication analysis of HvMTPs revealed one pair of segmental-like duplications in the barley genome. Evolutionary analysis suggested that barley MTPs underwent purifying natural selection. Additionally, the HvMTPs were analyzed in the pan-genome sequences of barley (20 accessions), which suggests that HvMTPs are highly conserved in barley evolution. Cis -acting regulatory elements, microRNA target sites, and protein–protein interaction analysis indicated the role of HvMTPs in a variety of biological processes. Expression profiling suggests that HvMTPs play an active role in maintaining barley nutrient homeostasis throughout its life cycle, and their expression levels were not significantly altered by abiotic stresses like cold, drought, or heat. The expression of barley HvMTP genes in the presence of heavy metals such as Zn 2+ , Cu 2+ , As 3+ , and Cd 2+ revealed that these MTPs were induced by at least one metal ion, implying their involvement in metal tolerance or transportation. The identification and comprehensive investigation of MTP gene family members will provide important gene resources for the genetic improvement of crops for metal tolerance, bioremediation, or biofortification of staple crops.

Heavy metal contamination in river water, sediment, groundwater and human blood, from Kanpur, Uttar Pradesh, India - Varsha Gupta; Dinesh Kumar; Anamika Dwivedi; Umesh Vishwakarma; D. S. Malik; Seema Paroha; Narendra Mohan; Neelima Gupta (Environmental Geochemistry and Health, 2023)

Bioengineering of biowaste to recover bioproducts and bioenergy: A circular economy approach towards sustainable zero-waste environment - Vinay Kumar; Alisa S. Vangnai; Neha Sharma; Komalpreet Kaur; Pritha Chakraborty; Mridul Umesh; Barkha Singhal; Divya Utreja; Edgar Uquiche Carrasco; Rodrigo Andler; Mukesh Kumar Awasthi; Mohammad J. Taherzadeh (Chemosphere, 2023)

Twenty-five years of Gondwana Research: A scientometric analysis - Riya Sureka; Umesh Bamel; Satish Kumar; Avik Sinha (Gondwana Research, 2023)

Differential Response of the Leaf Fruit Ratio and Girdling on the Leaf Nutrient Concentrations, Yield, and Quality of Nectarine - Vishal Singh Rana; Sayeed Ehsan Zarea; Sunny Sharma; Neerja Rana; Vijay Kumar; Umesh Sharma (Journal of Plant Growth Regulation, 2023)

Microbial engineering strategies for synthetic microplastics clean up: A review on recent approaches - Vinay Kumar; Neha Sharma; Lucky Duhan; Ritu Pasrija; Jithin Thomas; Mridul Umesh; Sivarama Krishna Lakkaboyana; Rodrigo Andler; Alisa S. Vangnai; Meththika Vithanage; Mukesh Kumar Awasthi; Wen Yi Chia; et al. (Environmental Toxicology and Pharmacology, 2023)

Genetic Variations in Tuber Dry Matter (%), Yield and Mineral Concentrations in a Diversity Panel of Tetraploid Potatoes - Baljeet Singh; Jagdev Sharma; Salej Sood; Vinay Bhardwaj; Sundaresha Siddappa; Dalamu; Hemant B. Kardile; Vineeta Sharma; Bhawna Dipta; Vinod Kumar; V. K. Dua; Umesh Goutam; et al. (Potato Research, 2023)

Aspects of the Current and Prospective Sustainable Usage of Nanofertilizers in Agriculture and Their Effects on Health of the Soil: an Updated Review - Manisha Negi; Saurabh Sharma; Uday Sharma; Pardeep Kumar; Umesh Sharma; Kapil Sharma (Journal of Soil Science and Plant Nutrition, 2023)

Underutilized fruit crops in North-Western Himalayan region under changing climatic scenario - Vishal Singh Rana; Sunny Sharma; Neerja Rana; Vijay Kumar; Umesh Sharma; Vaishali Modgill; Heerendra Prasad (Genetic Resources and Crop Evolution, 2023)

Mechanism of Cr(VI) reduction by an indigenous Rhizobium pusense CR02 isolated from chromite mining quarry water (CMQW) at Sukinda Valley, India - Hrudananda Sahoo; Kanika Kisku; Kumar S. K. Varadwaj; Prasannajit Acharya; Umesh Chandra Naik (Environmental Science and Pollution Research, 2023)

Pesticide contamination in agro-ecosystems: toxicity, impacts, and bio-based management strategies - Umesh Pravin Dhuldhaj; Rishikesh Singh; Vipin Kumar Singh (Environmental Science and Pollution Research, 2022)

Prediction of potential molecular markers of bovine mastitis by meta-analysis of differentially expressed genes using combined p value and robust rank aggregation - Anushri Umesh; Praveen Kumar Guttula; Mukesh Kumar Gupta (Tropical Animal Health and Production, 2022)

Insect pollinators of eggplant (Solanum melongena L.) in the Indian Himalayas and their role in enhancement of fruit quality and yield - Amit Umesh Paschapur; Sunaullah Bhat; A. R. N. S. Subbanna; Nirmal Kumar Hedau; Krishna Kant Mishra; Lakshmi Kant (Arthropod-Plant Interactions, 2022)

Dielectric studies for rare earth doped magnesium ferrite material - Umesh Chejara; Anamika Prajapati; Arvind Kumar (Environmental Science and Pollution Research, 2022)

Genotypic variations for tuber nutrient content, dry matter and agronomic traits in tetraploid potato germplasm - Baljeet Singh; Jagdev Sharma; Vinay Bhardwaj; Salej Sood; Sundaresha siddappa; Umesh Goutam; Dalamu; Hemant B. Kardile; Dipak Kumar; Vinod Kumar (Physiology and Molecular Biology of Plants, 2022)

Evaluation and characterization of EMS induced mutant population of Gossypium herbaceum - Umesh Kumar; Nilesh S. Chavan; Samir V. Sawant; Hemant Kumar Yadav (Vegetos, 2022)

Antioxidant properties, phenolics and flavonoids content of some economically important plants from North-west Indian Himalaya - Rajesh Kumar Sharma; Neha Sharma; Umesh Kumar; Sher Singh Samant (Natural Product Research, 2022)

Unified model using artificial neural network for high strength fibrous concrete subjected to elevated temperature - Syed Kaleem Afrough Zaidi; Md. Ayaz; Umesh Kumar Sharma (Innovative Infrastructure Solutions, 2022)

Bilinear elasto-dynamical response of SDOF system under sinusoidal loading - Govind Mohan; Umesh Kumar Pandey (Innovative Infrastructure Solutions, 2022)

Performance characteristics of rubberized concrete: a multipoint review - Gyanendra Kumar Chaturvedy; Umesh Kumar Pandey (Innovative Infrastructure Solutions, 2022)

Sialic Acid Conjugated Chitosan Nanoparticles: Modulation to Target Tumour Cells and Therapeutic Opportunities - Rafquat Rana; Sarita Rani; Vipin Kumar; Kartik T. Nakhate; Ajazuddin; Umesh Gupta (AAPS PharmSciTech, 2022)

Changing status of tropical cyclones over the north Indian Ocean - Medha Deshpande; Vineet Kumar Singh; Mano Kranthi Ganadhi; M. K. Roxy; R. Emmanuel; Umesh Kumar (Climate Dynamics, 2021)

Multivariate assessment of outflow water quality in highly urbanized creek system: implication of natural and anthropogenic processes - Umesh Kumar Pradhan; Anirudh Ram; Balaram Sahu; Udayakrishnan P. B.; Saurabh Lonkar; Laxmankumar Kumbhar (Environmental Science and Pollution Research, 2021)

Comparative photocatalytic dye and drug degradation study using efficient visible light–induced silver phosphate nanoparticles - Kaushal Kadiya; Sai Bhargava Vuggili; Umesh Kumar Gaur; Manu Sharma (Environmental Science and Pollution Research, 2021)

Synthesis of graphitic carbon nitride/cadmium sulfide core-shell nanofibers for enhanced photocatalysis - Sai Bhargava Vuggili; Kaushal Kadiya; Umesh Kumar Gaur; Manu Sharma (Environmental Science and Pollution Research, 2021)

Comparative CpG methylation kinetic patterns of cis-regulatory regions of heat stress–related genes in Sahiwal and Frieswal cattle upon persistent heat stress - Nitika Verma; Rafeeque R. Alyethodi; Ashima Kathuria; Rani Alex; Shaziya Hussain; Umesh Singh; S. Tyagi; Ajayvir Singh Sirohi; Sushil Kumar; Gyanendra S. Sengar; T. V. Raja; B. Prakash (International Journal of Biometeorology, 2021)

Distribution Pattern of the Benthic Meiofaunal Community Along the Depth Gradient of the Western Indian Continental Margin, Including the OMZ and Abyssal Plain - Sabyasachi Sautya; Santosh Gaikwad; Sanofar Khokher; Umesh Kumar Pradhan; Soumya Chatterjee; Amita Choudhury; Balaram Sahu; Suman Attri (Frontiers in Marine Science, 2021)
The continental margin harbors a variety of habitats that support incredible biodiversity and the function of their oceans' ecosystems. The meiofauna is considered a significant component of the benthic faunal community from the polar to the tropical regions. The meiofaunal community in the deep Indian Ocean, especially along the depth gradient, is poorly investigated. The present study aims to explore the benthic meiofaunal community structure along the depth gradients and its associated environment in the western Indian continental margin (WICM) and abyssal plain in the eastern Arabian Sea. Sediment samples were collected from seven different depths (111–3,918 m) along the WICM including the oxygen minimum zone (OMZ) and abyssal plain. A total of 22 taxa (groups) were encountered along the WICM. The nematodes (85%) were the most dominant taxa in all the depths, followed by copepods (11%), nauplii (5%), and polychaetes (1.36%). Our results suggest that (a) the organic matter has accumulated in OMZ sites; (b) a high amount of total organic carbon did not influence the meiofaunal density or biomass; (c) oxygen and depth gradients were significant drivers of the meiofaunal community, low levels of oxygen contributed to lower taxa diversity and density at 485 and 724 m depths; (d) a significant relationship of meiofaunal density and biomass with chloroplastic pigment equivalent (CPE) values indicates pelagic-benthic coupling. Copepods, nauplii, tanaidaceans, isopods, kinorhynchs, and cumaceans were affected by the low-oxygen conditions at the OMZ sites. Enhanced meiofaunal diversity, density, and biomass at deeper sites (non-OMZ-D) was attributed to increased abundance of copepods, nauplii, tanaidaceans, isopods, kinorhynchs, and cumaceans and were mostly concentrated on the surface sediment (0–4 cm) triggered by enhanced bottom-water oxygen and freshness of available food outside the OMZ except 3,918 m. Therefore, the present study showed the meiofaunal community pattern with respect to depth gradients and their related environmental changes, including the OMZ along the WICM and abyssal plain in the Arabian Sea. Based on this study, the future extent of these underestimated marine ecosystems must be considered a priority to understand its functional consequences.

An elaborative NMR based plasma metabolomics study revealed metabolic derangements in patients with mild cognitive impairment: a study on north Indian population - Umesh Kumar; Abhai Kumar; Smita Singh; Payal Arya; Sandeep Kumar Singh; Rameshwar Nath Chaurasia; Anup Singh; Dinesh Kumar (Metabolic Brain Disease, 2021)

Effect of moulding water content on strength characteristics of a cement-stabilized granular lateritic soil - Pawan Kumar Chamling; Dipti Ranjan Biswal; Umesh Chandra Sahoo (Innovative Infrastructure Solutions, 2021)

Apoptotic Effect and Anticancer Activity of Biosynthesized Silver Nanoparticles from Marine Algae Chaetomorpha linum Extract Against Human Colon Cancer Cell HCT-116 - Diptikanta Acharya; Sagarika Satapathy; Prathap Somu; Umesh Kumar Parida; Gitanjali Mishra (Biological Trace Element Research, 2021)

Validation of molecular response of tuberization in response to elevated temperature by using a transient Virus Induced Gene Silencing (VIGS) in potato - Maharishi Tomar; Sundaresha S.; Baljeet Singh; Vinay Bhardwaj; Salej Sood; Brajesh Singh; Neha Salaria; Kajal Thakur; Ashwani Kumar; Neha Sharma; Umesh Goutam (Functional & Integrative Genomics, 2021)

Effectiveness of Pongamia pinnata oil as rejuvenator for higher utilization of reclaimed asphalt (RAP) material - Sujit Kumar Pradhan; Umesh Chandra Sahoo (Innovative Infrastructure Solutions, 2020)

Characterization of a putative ribosome binding site at the 5′ untranslated region of bovine heat shock protein 90 - Rajib Deb; Gyanendra Singh Sengar; Vivek Junghare; Saugata Hazra; Umesh Singh; Rani Alex; Asish Kumar (Molecular Biology Reports, 2020)

Sources and implications of particulate organic matter from a small tropical river—Zuari River, India - Dearlyn Fernandes; Ying Wu; Prabhaker Vasant Shirodkar; Umesh Kumar Pradhan; Jing Zhang (Acta Oceanologica Sinica, 2020)

Transcriptome changes in reciprocal grafts involving watermelon and bottle gourd reveal molecular mechanisms involved in increase of the fruit size, rind toughness and soluble solids - Marleny Garcia-Lozano; Sudip Kumar Dutta; Purushothaman Natarajan; Yan R. Tomason; Carlos Lopez; Ramesh Katam; Amnon Levi; Padma Nimmakayala; Umesh K. Reddy (Plant Molecular Biology, 2020)

Characterizing binding sites of heat responsive microRNAs and their expression pattern in heat stressed PBMCs of native cattle, exotic cattle and riverine buffaloes - Pallavi Sharma; Ankita Sharma; Monika Sodhi; Preeti Verma; Kumari Parvesh; Shelesh K. Swami; Amandeep Jast; Umesh Kumar Shandilya; Manishi Mukesh (Molecular Biology Reports, 2019)

Nano-Co-Delivery of Berberine and Anticancer Drug Using PLGA Nanoparticles: Exploration of Better Anticancer Activity and In Vivo Kinetics - Iliyas Khan; Gaurav Joshi; Kartik T Nakhate; Ajazuddin; Raj Kumar; Umesh Gupta (Pharmaceutical Research, 2019)

Rootstock scion interaction effects on biochemical and gas exchange drought tolerant traits in arabica (Coffea arabica L.) coffee - Somashekhargouda Patil; D’Souza G. F; Deepika Kumar Umesh; C. Rudragouda (Plant Physiology Reports, 2019)

Prediction of Human Pharmacokinetics of Fomepizole from Preclinical Species Pharmacokinetics Based on Normalizing Time Course Profiles - Ravi Kumar Jairam; Sadanand Rangnathrao Mallurwar; Suresh P. Sulochana; Devaraj V. Chandrasekhar; Umesh Todmal; Ravi Kanth Bhamidipati; Wolfgang Richter; Nuggehally R. Srinivas; Ramesh Mullangi (AAPS PharmSciTech, 2019)

Interspecies comparative features of trichomes in Ocimum reveal insights for biosynthesis of specialized essential oil metabolites - Shiwani Maurya; Muktesh Chandra; Ritesh K. Yadav; Lokesh K. Narnoliya; Rajender S. Sangwan; Shilpi Bansal; Pankajpreet Sandhu; Umesh Singh; Devender Kumar; Neelam Singh Sangwan (Protoplasma, 2019)

Microbial Inoculants Assisted Growth of Chrysopogon zizanioides Promotes Phytoremediation of Salt Affected Soil - Umesh Pankaj; Durgesh Narain Singh; Geetu Singh; Rajesh Kumar Verma (Indian Journal of Microbiology, 2019)

Recycling of Organic Wastes in Agriculture: An Environmental Perspective - Bhavisha Sharma; Barkha Vaish; Monika; Umesh Kumar Singh; Pooja Singh; Rajeev Pratap Singh (International Journal of Environmental Research, 2019)

Self-Emulsifying Oral Lipid Drug Delivery Systems: Advances and Challenges - Sarita Rani; Rafquat Rana; Gaurav K. Saraogi; Vipin Kumar; Umesh Gupta (AAPS PharmSciTech, 2019)

Identification of structural requirements and prediction of inhibitory activity of natural flavonoids against Zika virus through molecular docking and Monte Carlo based QSAR Simulation - Sonam Bhargava; Tarun Patel; Ruchi Gaikwad; Umesh Kumar Patil; Shovanlal Gayen (Natural Product Research, 2019)

Correction to: Radiolabeled PLGA Nanoparticles for Effective Targeting of Bendamustine in Tumor Bearing Mice - Iliyas Khan; Avinash Gothwal; Ankur Kaul; Rashi Mathur; Anil Kumar Mishra; Umesh Gupta (Pharmaceutical Research, 2018)

Groundwater fluoride contamination, probable release, and containment mechanisms: a review on Indian context - Indrani Mukherjee; Umesh Kumar Singh (Environmental Geochemistry and Health, 2018)

Radiolabeled PLGA Nanoparticles for Effective Targeting of Bendamustine in Tumor Bearing Mice - Iliyas Khan; Avinash Gothwal; Ankur Kaul; Rashi Mathur; Anil Kumar Mishra; Umesh Gupta (Pharmaceutical Research, 2018)

HIV-1 Nef CAWLEAQ motif: a regulator of monocytes invasion through ENO1 modulation - Reshu Saxena; Umesh Kumar Vekariya; Pradeep Kumar; Amit Kumar Tripathi; Jimut Kanti Ghosh; Raj Kamal Tripathi (Molecular and Cellular Biochemistry, 2018)

Incipient motion for gravel particles in clay-silt-gravel cohesive mixtures - Zulfequar Ahmad; Umesh K. Singh; Ashish Kumar (Journal of Soils and Sediments, 2018)

Source apportionment of heavy metals and their ecological risk in a tropical river basin system - Balwant Kumar; Umesh Kumar Singh (Environmental Science and Pollution Research, 2018)

Three-dimensional velocity measurements around bridge piers in gravel bed - Manish Pandey; P. K. Sharma; Z. Ahmad; Umesh Kumar Singh; Nilav Karna (Marine Georesources & Geotechnology, 2018)

Characterization of hydrogeochemical process and evaluation of water quality of seven geothermal springs, Bakreswar, India - Subhajit Roy; Balwant Kumar; Abbhijit Chowdhury; Umesh Kumar Singh; Samit Ray (Arabian Journal of Geosciences, 2018)

Chitosan Engineered PAMAM Dendrimers as Nanoconstructs for the Enhanced Anti-Cancer Potential and Improved In vivo Brain Pharmacokinetics of Temozolomide - Ashok Kumar Sharma; Lokesh Gupta; Hitesh Sahu; Arem Qayum; Shashank K. Singh; Kartik T. Nakhate; Ajazuddin; Umesh Gupta (Pharmaceutical Research, 2018)

Evaluation of existing equations for temporal scour depth around circular bridge piers - Manish Pandey; P. K. Sharma; Z. Ahmad; Umesh Kumar Singh (Environmental Fluid Mechanics, 2017)

RT-LAMP assay: an alternative approach for profiling of bovine heat shock protein 70 gene in PBMC cultured model - Gyanendra Singh Sengar; Rajib Deb; T. V. Raja; Umesh Singh; Rajiv Kant; V. Bhanuprakash; R. R. Alyethodi; Sushil Kumar; Preetam Verma; Soumendu Chakraborty; Rani Alex; Rani Singh (Molecular Biology Reports, 2017)

Molecular Detection and Assessment of Hemato-Biochemistry, Oxidant/Antioxidant Status in Natural Canine Monocytic Ehrlichiosis Cases from Northern India - Suvendu Kumar Behera; Umesh Dimri; Parthasarathi Banerjee; Rajat Garg; Satyabrata Dandapat; Bhaskar Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Comparative expression profile of NOD1/2 and certain acute inflammatory cytokines in thermal-stressed cell culture model of native and crossbred cattle - V . Bhanuprakash; Umesh Singh; Gyanendra Singh Sengar; T. V. Raja; Basavraj Sajjanar; Rani Alex; Sushil Kumar; R. R. Alyethodi; Ashish Kumar; Ankur Sharma; Suresh Kumar; Bharat Bhusan; et al. (International Journal of Biometeorology, 2017)

Market-based incentives in developing countries: geographical dispersion, antecedents and implications of the Clean Development Mechanism - John Fay; Umesh Kumar (Climate and Development, 2017)

Cytosine deletion at AP2-box region of HSP70 promoter and its influence on semen quality traits in crossbred bulls - RAJIB DEB; BASAVRAJ SAJJANAR; UMESH SINGH; SUSHIL KUMAR; GYANENDRA SINGH SENGAR; RANI ALEX; A. K. DAS; S. TYAGI; T. V. RAJA; R. R. ALYETHODI; RANI SINGH; V. BHANUPRAKASH; et al. (Journal of Genetics, 2016)

Preparation and Preclinical Evaluation of Inhalable Particles Containing Rapamycin and Anti-Tuberculosis Agents for Induction of Autophagy - Anuradha Gupta; Deepak Sharma; Jairam Meena; Sanketkumar Pandya; Madhur Sachan; Sadan Kumar; Kavita Singh; Kalyan Mitra; Sharad Sharma; Amulya K. Panda; Pushpa Gupta; Umesh Datta Gupta; et al. (Pharmaceutical Research, 2016)

Effect of energy and protein levels on nutrient utilization and their requirements in growing Murrah buffaloes - Sonali Prusty; Shivlal Singh Kundu; Goutam Mondal; Umesh Sontakke; Vijay Kumar Sharma (Tropical Animal Health and Production, 2016)

Pyrazolo[3,4-d]pyrimidines as the inhibitors of mycobacterial β-oxidation trifunctional enzyme - Umesh Yadava; Bindesh Kumar Shukla; Mihir Roychoudhury (Medicinal Chemistry Research, 2015)

Understanding the mechanisms of ATPase beta family genes for cellular thermotolerance in crossbred bulls - Rajib Deb; Basavaraj Sajjanar; Umesh Singh; Rani Alex; T. V. Raja; Rafeeque R. Alyethodi; Sushil Kumar; Gyanendra Sengar; Sheetal Sharma; Rani Singh; B. Prakash (International Journal of Biometeorology, 2015)

SNPs at exonic region of aquaporin-7 (AQP7) gene may affect semen quality parameters among crossbred bulls - SUSHIL KUMAR; RAJIB DEB; UMESH SINGH; INDRAJIT GANGULY; D. K. MANDAL; RUPALI SINGH; SHEETAL SHARMA; GYANENDRA SENGAR; RANI SINGH; MAHESH KUMAR; ARJAVA SHARMA (Journal of Genetics, 2015)

Genetic diversity and association mapping of bacterial blight and other horticulturally important traits with microsatellite markers in pomegranate from India - Nripendra Vikram Singh; Venkata Lakshmi Abburi; D. Ramajayam; Ravinder Kumar; Ram Chandra; Kuldeep Kumar Sharma; Jyotsana Sharma; K. Dhinesh Babu; Ram Krishna Pal; Dhananjay M. Mundewadikar; Thangasamy Saminathan; Robert Cantrell; et al. (Molecular Genetics and Genomics, 2015)

Heterozygosity at the SNP (rs136500299) of ITGB6 receptor gene possibly influences the susceptibility among crossbred bull to foot and mouth disease infection - Rani Singh; Rajib Deb; Umesh Singh; T. V. Raja; Rani Alex; Sushil Kumar; Soumendu Chakraborti; Rafeeque R. Alyethodi; Sheetal Sharma; Gyanendra Sengar (VirusDisease, 2015)

Improvement in the yield and quality of kalmegh ( Andrographis paniculata Nees) under the sustainable production system - Rajesh Kumar Verma; Sanjeet K. Verma; Umesh Pankaj; Anand K. Gupta; Khushboo Khan; Karuna Shankar (Natural Product Research, 2015)

Development of a tetra-primer ARMS PCR-based assay for detection of a novel single-nucleotide polymorphism in the 5′ untranslated region of the bovine ITGB6 receptor gene associated with foot-and-mouth disease susceptibility in cattle - Rani Singh; Rajib Deb; Umesh Singh; Rani Alex; Sushil Kumar; Soumendu Chakraborti; Sheetal Sharma; Gyanendra Sengar; Rupali Singh (Archives of Virology, 2014)

Alterations in oxidant/antioxidant balance, high-mobility group box 1 protein and acute phase response in cross-bred suckling piglets suffering from rotaviral enteritis - Ujjwal Kumar De; Reena Mukherjee; Sukdeb Nandi; Bhimnere Hanumatnagouda Manjunatha Patel; Umesh Dimri; Chintu Ravishankar; Ashok Kumar Verma (Tropical Animal Health and Production, 2014)

Design and syntheses of some new quinoxaline derivatives containing pyrazoline residue as potential antimicrobial agents - Jagdish Kumar; Gita Chawla; Umesh Kumar; Kapendra Sahu (Medicinal Chemistry Research, 2014)

Residual feed intake as a feed efficiency selection tool and its relationship with feed intake, performance and nutrient utilization in Murrah buffalo calves - Bisitha Kattiparambil Subhashchandra bose; Shivlal Singh. Kundu; Nguyen Thi Be Tho; Vijay Kumar Sharma; Umesh Balaji Sontakke (Tropical Animal Health and Production, 2014)

Molecular dynamics simulation of DNA duplex, analog of PPT (polypurine tract), its conformation and hydration: a theoretical study - Ramesh Kumar Yadav; Umesh Yadava (Medicinal Chemistry Research, 2014)

Integrated Effect of Organic and Inorganic Fertilizers on Yield, Quality Parameter and Nutrient Availability of Sugarcane in Calcareous Soil - U. N. Umesh; Vipin Kumar; M. Alam; S. K. Sinha; Khusboo Verma (Sugar Tech, 2013)

A pilot study on water pollution and characterization of multidrug-resistant superbugs from Byramangala tank, Ramanagara district, Karnataka, India - Sinosh Skariyachan; Priyanka Lokesh; Reshma Rao; Arushi Umesh Kumar; Kiran S. Vasist; Rajeswari Narayanappa (Environmental Monitoring and Assessment, 2013)

Morphometric Analysis and Identification on Specific Metric Characters Pertaining Growth of the Osteobrama cotio of the Brahmaputra, Barak and Teesta River of North Eastern Himalayan River Systems - Konthoujam Shyam Kumar; Umesh Chandra Goswami (Proceedings of the Zoological Society, 2013)

Physically-based distributed soil erosion and sediment yield model (DREAM) for simulating individual storm events - RAAJ Ramsankaran; Umesh Chandra Kothyari; Sanjay Kumar Ghosh; Andreas Malcherek; Krishnan Murugesan (Hydrological Sciences Journal, 2013)

Amelioration of altered oxidant/antioxidant balance of Indian water buffaloes with subclinical mastitis by vitamins A, D3, E, and H supplementation - Umesh Dimri; Mahesh Chandra Sharma; Shanker K. Singh; Pankaj Kumar; Ricky Jhambh; Bishwambhar Singh; Samiran Bandhyopadhyay; Med Ram Verma (Tropical Animal Health and Production, 2013)

Stabilization of a Clayey Soil with Fly Ash and Lime: A Micro Level Investigation - Neeraj Kumar Sharma; S. K. Swain; Umesh C. Sahoo (Geotechnical and Geological Engineering, 2012)

A qualitative study on sea surface temperature over the tropical Indian Ocean and performance of Indian summer monsoon - Umesh Kumar Singh; Gyan Prakash Singh (Theoretical and Applied Climatology, 2012)

Psoroptes cuniculi induced oxidative imbalance in rabbits and its alleviation by using vitamins A, D3, E, and H as adjunctive remedial - Shanker Kumar Singh; Umesh Dimri; Mahesh Chandra Sharma; Devendra Swarup; Mritunjay Kumar; Ramesh Tiwary (Tropical Animal Health and Production, 2012)

The curative and antioxidative efficiency of ivermectin and ivermectin + vitamin E-selenium treatment on canine Sarcoptes scabiei infestation - Suvendu Kumar Behera; Umesh Dimri; Shanker Kumar Singh; Ranjan Kumar Mohanta (Veterinary Research Communications, 2011)

Chemical composition of rain water and influence of airmass trajectories at a rural site in an ecological sensitive area of Western Ghats (India) - Jetta Satyanarayana; Loka Arun Kumar Reddy; Monika Jain Kulshrestha; R Nageswara Rao; Umesh Chandra Kulshrestha (Journal of Atmospheric Chemistry, 2010)

Assessment of the impact of landfill on groundwater quality: A case study of the Pirana site in western India - Umesh Kumar Singh; Manish Kumar; Rita Chauhan; Pawan Kumar Jha; AL. Ramanathan; V. Subramanian (Environmental Monitoring and Assessment, 2008)

Analysis of the initiator tRNA genes from a slow- and a fast-growing mycobacterium - Anahita Dastur; Pradeep Kumar; Sneha Ramesh; Mundodi Vasanthakrishna; Umesh Varshney (Archives of Microbiology, 2002)

Properties of an extracellular amylase purified from a Bacillus species - Vatsala Maitin; R. Kavitha; S. Umesh-Kumar (World Journal of Microbiology and Biotechnology, 2001)

Short-Term Water Demand Forecast Modelling at IIT Kanpur Using Artificial Neural Networks - Ashu Jain; Ashish Kumar Varshney; Umesh Chandra Joshi (Water Resources Management, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

The effect of ethanol on cell wall antigens ofSaccharomyces cerevisiae and specific isolation of high ethanol producing strains of this yeast, making use of a serological technique - S. Umesh-Kumar; L. Nagarajan; F. Rehana; Krishna Nand (Antonie van Leeuwenhoek, 1990)